Incorporating online reference in teaching photographic education for photography students / Wan Nor Ayuni Wan Mohd Zain - Wan Mohd Zain, Wan Nor Ayuni (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
In a visual world where messages are often carried by visual means, our attitude towards photography is changing to accepting the potential of the beyond its factuality. The challenge facing photography instruction today, is teaching photographers to be visually literate. The goal is to introduce a theoretical element within practical photography instruction which will enable students to gain the skills of visual literacy - 'reading' photographs in addition to 'writing' them. This product presents a mechanism in which the online reference and instruction is not aimed to replace the traditional on campus activities but to enhance toward the effectiveness for teaching photography, that would not have been possible to achieve because of the class time limitations and the nature of the courses. The online reference model is aimed incorporate theoretical layer which would develop student's digest and understanding for better learning situations, further on to increase competencies becoming professional photographic practitioners.